5‐Formyluridine and Its Synthetic Applications. Issue 45 (1st December 2022) - Kumar, Sandeep; Kumar, Sumit; Arora, Aditi; Prasad, Ashok K.; Maity, Jyotirmoy
Abstract: In recent decades, 5‐formyluridine has drawn attention of the researchers working in the field of nucleic acid chemistry due to its role as key intermediate for the synthesis of modified nucleosides. Numerous efficient and facile synthetic methods have been developed for the synthesis of this molecule and this nucleoside precursor has further been explored for the synthesis of modified nucleosides and nucleotides. These compounds have showed significant biological activities against tumor cell lines, bacterial and viral strains, etc. Herein, a complete account of synthesis of 5‐formyluridine, its application for the synthesis and biological activities is presented. Abstract : 5‐formyluridine has emerged as a key intermediate for the production of modified nucleoside monomers affixed with variety of structural and functional moieties. We believe that this review will draw the attention of the researchers working in the field of nucleoside chemistry towards this important key intermediate for further development of synthetic methodologies and exploration of this molecule for designing complex nucleoside monomers.